¿Es efectivo aplicar el programa Doctores de los suelos en el sector productivo argentino? - Carfagno, Patricia; Sainz, Daiana Soledad; Beltran, Marcelo Javier; Jecke, Fernando Ariel; Santia, Gonzalo; Accame, M.F. (AAPRESID, 2025)
Poster